Lived Experiences of Patients Following Myocardial Infarction Diagnosis in an Impoverished region in Pakistan‒A Qualitative Study - Amtul Noor; Ata Ul Haiy; Amtul Sami; Muhammad Masudul Hasan Nuri (International Journal of Medical Students)
BACKGROUND: Cardiovascular disease (CVD) is a leading cause of death worldwide, accounting for 19 million deaths in 2020 alone. Ischemic heart disease being the leading cause of CVD-related health impairment worldwide impacts an individual's social, physical, economic, and psychological well-being significantly. Socioeconomic factors such as poverty, inflation, and literacy rates can impact individual experiences of Myocardial infarction (MI). Given the limited awareness and facilities in smaller regions of Pakistan, this study aims to explore the lived experiences of individuals following MI, in a district general hospital in Pakistan covering a large geographical area.